2008
DOI: 10.1086/524840
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Collisional Evolution of Debris Disks

Abstract: Infrared surveys indicate that the dust content in debris disks gradually declines with stellar age. We simulated the long-term collisional depletion of debris disks around solar-type (G2 V) stars with our collisional code. The numerical results were supplemented by, and interpreted through, a new analytic model. General scaling rules for the disk evolution are suggested. The timescale of the collisional evolution is inversely proportional to the initial disk mass and scales with radial distance as r 4.3 and w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
325
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(362 citation statements)
references
References 59 publications
34
325
3
Order By: Relevance
“…As an example, a disc with h = 0.04 could harbour embryos as large as a few 100 km. As a matter of fact, we subscribe to the theoretical arguments supporting the presence of large hidden bodies, which are in particular needed to provide the mass reservoir for sustaining the high collisional activity of debris discs (Löhne et al 2008). What we have demonstrated is that direct observational evidence can probably not be easily obtained, since for aspect ratios lower than ∼0.06 there is no direct link between vertical thickness and the dynamical excitation of the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, a disc with h = 0.04 could harbour embryos as large as a few 100 km. As a matter of fact, we subscribe to the theoretical arguments supporting the presence of large hidden bodies, which are in particular needed to provide the mass reservoir for sustaining the high collisional activity of debris discs (Löhne et al 2008). What we have demonstrated is that direct observational evidence can probably not be easily obtained, since for aspect ratios lower than ∼0.06 there is no direct link between vertical thickness and the dynamical excitation of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical studies of debris discs fall into two main categories: those investigating the collisional and size distribution evolution of the system are usually statistical particle-in-the-box models, of no or poor spatial resolution and very limited dynamical evolution (e.g., Krivov et al 2006;Thébault & Augereau 2007;Löhne et al 2008), while those studying the dynamics and the formation and evolution of spatial structures are mostly N-body type codes, where size distributions and mutual collisions are usually neglected (see for example Reche et al 2008).…”
Section: Modelmentioning
confidence: 99%
“…During the inside-out stirring, different annular regions in a disk brighten up and enter their erosive debris disk phase. Their individual fractional luminosities decay more slowly than 1/t (Dominik & Decin 2003;Wyatt et al 2007;Trilling et al 2008;Löhne et al 2008). However, this decay is even more rapid than the outward migration of the stirring front.…”
Section: Disk Evolutionmentioning
confidence: 99%
“…2), and so a higher collision rate at the collision point and along the anti-collision line expected to start with the shape it tends to in steady state. Both are valid criticisms, but their consequences can be readily accounted for (Löhne et al 2008;Wyatt et al 2011). Furthermore, it is found that the simple prescription given above is usually accurate to within a factor of a few and so is acceptable for many applications.…”
Section: Collisional Evolutionmentioning
confidence: 99%
“…However, this is not interpreted as giant impact debris. Rather, this dust is believed to be the product of steady state collisional grinding of planetesimal belts that are analogous to the Kuiper Belt in the Solar System (Wyatt et al 2007b;Löhne et al 2008;Gáspár et al 2013). At the large orbital separations inferred for these belts, collisional lifetimes are long enough that their dust can persist several Gyr above the detection threshold.…”
Section: Collisions At Larger Separationsmentioning
confidence: 99%